Foot Placement Indicator for Balance of Planar Bipeds with Point Feet. (17th May 2013) - van Zutven, Pieter; Nijmeijer, Henk
Abstract If humanoid robots are to be used in society, they should be able to maintain their balance. Knowing where to step is crucially important. In this paper we contribute an algorithm that can compute the foot step location such that bipedal balance is maintained for planar bipeds with point feet and an arbitrary number of non-massless links on a horizontal and flat ground. The algorithm is called the foot placement indicator (FPI) and it extends the foot placement estimator (FPE). The FPE uses an inverted pendulum model to capture the dynamics of a humanoid robot, whereas the FPI deals with multi-body models with distributed masses. This paper analyses equilibrium sets and the stability of planar bipeds with point feet. The algorithm uses conservation of energy throughout the step, taking into account the instantaneous impact dynamics at foot strike. A simulation case study on a five-link planar biped shows the effectiveness of the FPI.